Effects of 4-Hydroxybenzaldehydeon on Interactions With Neurovascular Unit-Related Cells - Yang Yuan; Dai Rong (Polskie Towarzystwo Farmaceutyczne, 2024)
4-hydroxybenzaldehyde (4-HBd) is one of the active compounds with neuroprotective effects, which has been confirmed to have anti cerebral ischemical reperfusion injury (CIRI) effect in previous study. In this study, we explored the protective effect of 4-HBd on the neurovascular unit (NVU) after CIRI and its mechanism through in vivo and in vitro experiments. Establish rat of middle cerebral artery occlusion/reproduction (MCAO/R) model, transwell chamber was used to establish an in vitro primary cell co-culture model to simulate NVU, causing oxygen glucose deprivation/reperfusion (OGD/R) injury, simulating the pathological of CIRI in vivo. Longa 5-point method was used to evaluate the neurological function of the rats, and transmission electron microscope was used to observe the ultrastructural changes of NVU. Western Blot was used to detect the expression of neuronal protein in rat brain. The mRNA expressions of ang-1/tie-2 signaling pathway and bdnf/trkb signaling pathway were detected by qPCR. In vivo results showed that 4-HBd reduced neurological function scores and improved the ultrastructure of NVU after MCAO/R rats. 4-HBd could up-regulate the expression of microtubule associated protein-2 (Map-2), glial fibrillary acidic protein (GFAP) and occludin. In vitro results showed that 4-HBd could activate ang-1/tie-2 signaling pathway, increased occludin mRNA expression and protect the blood brain barrier (BBB). 4-HBd can activate bdnf/trkb signaling pathway, up-regulate map-2 mRNA expression, and promote neuronal repair. In vitro and in vivo results indicated 4-HBd can affect the ang-1/tie-2 and bdnf/trkb signaling pathways, and BBB damage is alleviated and NVU homeostasis is maintained to improve CIRI.